Yeast KEOPS complex regulates telomere length independently of its t6A modification function. (20th May 2018) - Liu, Ying-Ying; He, Ming-Hong; Liu, Jia-Cheng; Lu, Yi-Si; Peng, Jing; Zhou, Jin-Qiu
Abstract: In Saccharomyces cerevisiae, the highly conserved Sua5 and KEOPS complex (including five subunits Kae1, Bud32, Cgi121, Pcc1 and Gon7) catalyze a universal tRNA modification, namely N 6 -threonylcarbamoyladenosine (t 6 A), and regulate telomere replication and recombination. However, whether telomere regulation function of Sua5 and KEOPS complex depends on the t 6 A modification activity remains unclear. Here we show that Sua5 and KEOPS regulate telomere length in the same genetic pathway. Interestingly, the telomere length regulation by KEOPS is independent of its t 6 A biosynthesis activity. Cytoplasmic overexpression of Qri7, a functional counterpart of KEOPS in mitochondria, restores cytosolic tRNA t 6 A modification and cell growth, but is not sufficient to rescue telomere length in the KEOPS mutant kae1 Δ cells, indicating that a t 6 A modification-independent function is responsible for the telomere regulation. The results of our in vitro biochemical and in vivo genetic assays suggest that telomerase RNA TLC1 might not be modified by Sua5 and KEOPS. Moreover, deletion of KEOPS subunits results in a dramatic reduction of telomeric G-overhang, suggesting that KEOPS regulates telomere length by promoting G-overhang generation. These findings support a model in which KEOPS regulates telomere replication independently of its function on tRNA modification.